Behavioral nutrition: Intuitive eating as an approach to managing dysfunctional eating behaviors in adolescence (Research, Society and Development, 2025)
This study presents the approach of intuitive eating in managing dysfunctional eating behaviors among adolescents. Adolescence is a period characterized by biological, psychological, and social changes that can influence eating habits and increase vulnerability to the development of eating disorders. In this context, intuitive eating emerges as an effective approach to promoting a healthier relationship with food by encouraging self-regulation and reducing practices such as dietary restriction and binge eating. The objective of this study was to conceptualize intuitive eating, identify factors that contribute to dysfunctional eating behaviors, and evaluate the impact of this approach on adolescents’ self-regulation of eating. The methodology adopted was a narrative literature review, analyzing articles, books, and dissertations related to the topic. The platforms used for the research included: SciELO, PubMed, Lume UFRGS, RBONE, Archives of Health, Nestlé, Hormone Research, ResearchGate, St. Martin’s Griffin, Vita et Sanitas, Public Health Nutrition, Research, Society and Development, Revista de Pesquisa UNIRIO, Contribuciones a las Ciencias Sociales, RI UFPE, Unicesumar, Institutional Knowledge Repository, and Sextante. The results indicate that practices such as intuitive eating can improve body image perception, promote physical and psychological well-being, and strengthen one's relationship with food. It is concluded that intuitive eating is a promising strategy for preventing and treating dysfunctional eating behaviors, especially when guided by nutrition professionals.